The logistics and transportation review (Ann Arbor, Mich. : University Microfilms International, 1977)
'An international journal published in Berkeley California, and in Vancouver, Canada by the Faculty of Commerce and Business Administration, University of British Columbia.'
vol. 13-25 (1977-1989).
Includes index.
Continues Logistics Review (Berkeley), which was issued 1965-66 as The Logistics Review and Military Logistics Journal.
Requires the use of a microfiche reader.
Keywords: Logistics -- Periodicals; Transportation -- Periodicals